GAGASAN KEDUDUKAN LAYANAN SEKSUAL SEBAGAI BENTUK TINDAK PIDANA GRATIFIKASI: STUDI KASUS INDONESIA DAN SINGAPURA - Muhammad Fadhil; Putra, Muhammad Reffarm Dwi (Penerbit Universitas Atma Jaya Yogyakarta, 2025)
This research examines the anti-corruption regulations implemented in Indonesia and Singapore by emphasising the use of sexual services in the crime of gratification. This is triggered by the development of modus operandi in the crime of gratification, so that it no longer uses conservative methods, but leads to the use of women as ‘currency’ aimed at advancing one's interests. The use of this modus operandi can be categorised as a conflict according to the moral priciples upheld in society and human rights. However, this modus operandi is not explicitly regulated in the Anti-Corruption Law and the Prevention of Corruption Act. The present research looks further into the position as a criminal act involving sexual services of gratification. This research is a normative legal study based on secodary data gathered through library research. It utilitizes conceptual approach, case approach, and comparative approach to examine norms and rules related to the legal status of sexual services as a form of criminal gratification. This research concludes that the position of sexual services can be categorised as an object of criminal act of gratification in the phrase “other facilities”. This can be reviewed using extensive interpretation and using the concept of progressive law. So that sexual services may be considered in the object regarding benefits received within the context of form related to other facilities.